PENERAPAN METODE K-MEDOIDS CLUSTERING PADA PENANGANAN KASUS DIARE DI INDONESIA - Fitriani Hardiyanti; Heru Satria Tambunan; Ilham Syaputra Saragih (STMIK Budi Darma, 2019)
Diarrhea is a condition in which a person defecates in a runny or liquid form and occurs repeatedly. Diarrhea can cause the loss of large amounts of water and substances needed by the body. Diarrhea is one of the health problems in developing countries, especially in Indonesia both in urban and rural areas. Diarrhea morbidity rates around 200-400 occurrences among 1000 residents each year. Thus in Indonesia there can be around 60 million incidents each year, most (70-80%) of these sufferers are children under five years (BALITA). Some patients (1- 2%) will fall into dehydration and if not immediately helped 50-60% of them can die. This group experiences more than one incidence of diarrhea every year. K-Medoids Algorithm Clustering is one of the algorithms used for to group data.Keywords: Data Mining, K-Medoids, Clustering, Diarrhea